Tableau vivant et postmodernité : quelles affinités ? - Halimi, Carole (RACAR : Revue d'art canadienne / Canadian Art Review, 2019)
This article investigates the relationship of the tableau vivant to modernism and postmodernism and examines how the aesthetic characteristics mobilized by the tableau vivant disrupt the logic of modernism. In the nineteenth century, the tableau vivant, because of its intrinsic intermediality, was seen as overly theatrical and was thus relegated to the antechamber of photographic modernity, as a practice that discredited the seriousness of a medium in need of legitimization. By 1964, however, Robert Morris used the tableau vivant as an instrument to critique modernism in his work Site. Postmodernist artists explored the tableau vivant still further and used it repeatedly in photography, video, and performance. This article examines how Luigi Ontani, Cindy Sherman, and Yasumasa Morimura adopt the tableau vivant as an interface that allows them to physically manipulate representations of Western society in order to critique its values and codes.